2020
DOI: 10.1111/jonm.13054
|View full text |Cite
|
Sign up to set email alerts
|

Nurse managers in perioperative settings and their reasons for remaining in their jobs: A qualitative study

Abstract: Aim The study describes what helps nurse managers maintain the strength to keep going as leaders. Background Good leadership is important for the quality of patient care, patient satisfaction in care and efficiency. Many nurse managers stay on despite challenges at work. Methods Twelve nurse managers were interviewed. Data were analysed by systematic text condensation according to Malterud. Results The results were as follows: A—Walking side by side with my employees; B—Knowing that I mean something to my empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…This implies that participants that rate their work environment as positive and feel that they can influence it also rate the management as kind and considerate and feel that they give feedback on time. This is well in line with previous results from a qualitative study from the present workplace, which reported that feedback is one of the important factors for the successful implementation of the model [ 52 ]. The results also suggest that there is a connection between experiencing that one has a manager who takes one’s viewpoint into consideration and experiencing that one’s productivity is not affected by factors in the work environment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This implies that participants that rate their work environment as positive and feel that they can influence it also rate the management as kind and considerate and feel that they give feedback on time. This is well in line with previous results from a qualitative study from the present workplace, which reported that feedback is one of the important factors for the successful implementation of the model [ 52 ]. The results also suggest that there is a connection between experiencing that one has a manager who takes one’s viewpoint into consideration and experiencing that one’s productivity is not affected by factors in the work environment.…”
Section: Discussionsupporting
confidence: 92%
“…The positive changes seen in the present study occurred in a workplace that had just been through a reorganisation, which usually has negative consequences, both on employees’ health and on how they experience the work situation [ 44 , 45 ]. This strengthens previous findings that the Stamina model supports positive leadership and employee participation [ 37 , 52 , 58 ], which are factors that have been proven to counteract the negative effects of reorganisation [ 29 , 51 ]. Here, the improvements in HRI and productivity could possibly be attributed to the reorganisation itself or positive changes in the management team, but none of those factors emerged as important factors in previous qualitative studies in the current working group [ 52 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Qualitative design is commonly used to study people's experiences of a phenomenon or a topic (Malterud, 2001, 2012, 2016). The study had a qualitative and prospective design and is a part of a larger research programme on nurse managers’ work environments (Arakelian et al., 2020). Individual interviews were carried out with seven perioperative nurse managers who had left their position during the last 6–12 months.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, a study by Arakelian et al. (2020) demonstrated that nurse managers found their way and their inspiration as leaders through their employees’ strengths and motivation, and this was the driving force to stay. Saifman and Sherman (2019) put forward the link between the nurse manager's workload and role retention.…”
Section: Introductionmentioning
confidence: 99%